A hybrid framework for integrating multiple manufacturing clouds. Issue 1 (September 2016) - Yang, Chen; Shen, Weiming; Lin, Tingyu; Wang, Xianbin
Abstract Cloud manufacturing (CMfg) adopts and extends the concept of cloud computing to make mass Manufacturing Resources and Capabilities (MR/Cs) more widely integrated and accessible to users through the Internet. However, a single manufacturing cloud (MC) has limited MR/Cs, due to both economic and technical constraints, and can only provide limited manufacturing services in terms of function, price, and reliability, etc. Using the aggregated MR/Cs or services of multiple MCs is a natural evolution, i.e., MCs can satisfy peak demands for MR/Cs through collaboration, while users can have a wider selection of services from multiple MCs. To address such requirements, we propose a hybrid framework for integrating multiple MCs. The key functional modules and the business models of the proposed framework are presented to guide future integration of MCs. The enabling technologies, such as semantic web and ontologies, intelligent agents, service-oriented architecture, and materials handling and logistics technologies are also discussed. A case study is given, showing the feasibility and rationality of the proposed approach.